Pengaruh Teknologi Fintech dalam Transformasi Industri Asuransi dan Implikasi Regulasi di Indonesia - Vania Armilda Sari Nugroho; Luki Kurniawan (Hakim, 2024)
This research discusses the impact of FinTech technology on the transformation of the insurance industry and the regulatory implications in Indonesia. FinTech has changed the payment system in society and helped companies in the financial sector. FinTech offers a variety of financial services that were previously exclusive to banks. Explains how digital banking works, including FinTech infrastructure related to peer-to-peer payments, mobile applications, cryptocurrency transfers, digital lending models, mass investments, robo advisors, artificial intelligence, and advanced analytics. The method used in this research is a normative juridical approach, with analytical descriptive specifications, while data collection techniques use primary data and secondary data. This research aims to determine the extent of the influence of Fintech Technology on the transformation of the insurance industry and its implications for regulations in Indonesia.